STRATEGI DIAGNOSTIK GURU PAUD DALAM MENGIDENTIFIKASI HAMBATAN PERKEMBANGAN ANAK - Aphina Wulan Kunanti; Sauma Fitri; Nabila Rahmah; Sitti Ulviani; Maya Rosita Urza; Faizatul Faridy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the diagnostic strategies used by Early Childhood Education (ECE) teachers in identifying children's developmental barriers based on scientific literature reviews. This research is motivated by the importance of early detection of developmental barriers in early childhood to support appropriate intervention and educational services according to children's developmental needs. The study employed a qualitative library research method through the analysis of 15 relevant scientific literature sources, including national journals, international journals, conference proceedings, and research reports published between 2017 and 2025. Data collection techniques were conducted through documentation and content analysis of various studies related to the diagnostic strategies of ECE teachers. The findings revealed that ECE teachers' diagnostic strategies were carried out through child development observation, diagnostic assessment, the use of developmental screening instruments, developmental record documentation, communication with parents, and collaboration with professionals and inclusive education institutions. The most frequently identified developmental barriers included speech delay, language and communication disorders, social-emotional difficulties, hyperactivity, and motor development delays. This study concludes that the success of identifying children's developmental barriers is strongly influenced by teachers' competencies, systematic developmental assessments, support for inclusive education, and parental involvement in the child development process.